Need Assessment of ICT Skills Training of Principals in Federal Government Secondary Schools - Asma Ibrahim; Mehnoor Arshad; Wajahat Hussain, (Dialogue Social Science Review (DSSR), 2024)
Information and communication technology become an integral part of managerial task of principals. This study assesses the training need of Information and Communication Technology (ICT) skills of principals in FG schools for improved performance. The main objectives of research study were to identify the importance of ICT skills for educational managers and their competence level of ICT skills. These objectives were achieved through Likert scale designed survey conducted in Federal Government Secondary schools of Islamabad and Rawalpindi. Primary data were collected through survey form principals. Questionnaire was used to collect data from principals. Data were collected from the whole population. No sampling was done. The data collection was carried through questionnaire personally, via email and mail. Findings of the study showed that training of ICT skills of the principals is needed for better management of institutions. It may be concluded that research provides significant contribution to the concerned departments to work on the enhancement of ICT skills of their heads of institutions to make them self-reliant.